Significance of mouse xenograft tumor model using patient-derived cancer organoids for clinical drug development - Ogawa, Hisataka; Yoshida, Keiichi; Hasegawa, Shinichiro; Wada, Hiroshi; Yasui, Masayoshi; Tahara, Hideaki (Frontiers in Oncology, 2025)
BackgroundIn vitro and in vivo preclinical examinations of cancer cell lines are performed to determine the effectiveness of new drugs before initiating clinical trials. However, there is often a significant disparity between the promising results observed in preclinical evaluations and actual outcomes in clinical trials. Therefore, we hypothesized that this inconsistency might be due to the differences between the characteristics of cell lines and actual cancers in patients. Therefore, we screened drugs for bile duct cancer to test our hypotheses.MethodsWe established patient-derived cancer organoids (PDCOs) from the surgical samples of patients with bile duct cancer and conducted multiple in vitro drug screening tests.ResultsWe identified proteasome inhibitors (Bortezomib and Carfilzomib) as promising drugs in the screening. Bortezomib has demonstrated a significant antitumor effect on bile duct cancer cell-derived xenografts, as previously reported in preclinical trials. However, although Bortezomib showed significant proliferation inhibition in PDCOs in three-dimensional culture in vitro, it did not exhibit significant anti-tumor effects in mouse xenograft tumor models using our PDCOs. Bile duct cancer cell-line-derived xenografts are characterized by structurally uniform, irregular glandular structures surrounded by simple and sparse stromal components. However, organoid-derived xenografts exhibit a spectrum of differentiation levels within irregular glandular structures and consist of a complex and rich stromal microenvironment similar to those observed in surgical specimens.ConclusionThese findings suggest that in vivo studies using PDCO xenograft tumor models may be more suitable than conventional mouse tumor models for determining the clinical development of drugs.